COMPARISON OF PHOTON-COUNTING AND FLAT-PANEL DIGITAL MAMMMOGRAPHY FOR THE PURPOSE OF 3D IMAGING USING A NOVEL IMAGE PROCESSING METHOD. Issue 3 (29th July 2021) - Svahn, T M; Gordon, R; Ast, J C; Riffel, J; Hartbauer, M
Abstract: The purpose of the present work was to compare the quality of low-dose projections from a photon-counting with a flat-panel system, and to evaluate a novel image processing method. Images were acquired of phantoms in both systems at average glandular doses ranging from ~ 0.15 to 1.4 mGy. Automated detection of low-contrast features and modulation transfer functions were evaluated in phantom images. The novel image processing method was compared with standard processing in a series of clinical cases. At low-doses (~0.15) the photon-counting system out-performed the flat-panel system with a much higher detectability of low-contrast features. The novel algorithm was superior to both manufacturers' processing in terms of conspicuity of soft-tissue lesions ( p  > 0.05), whereas it was not significantly different in calcification conspicuity. Photon-counting should allow more low-dose projections to be acquired at the same total dose. The novel image enhancer can help to further increase the image quality.